Studying nitrogen influence on efficiency of vibrocavitation treatment of dairy factory wastewater - Шевчук, Лілія Іванівна; Афтаназів, Іван Семенович; Строган, Орися Іванівна; Предзимірська, Леся Михайлівна (Eastern-European Journal of Enterprise Technologies, 2014)
Creating highly efficient methods of wastewater decontamination and destruction of present organic compounds is one of the promising trends for solving problems in technology of water treatment. The technology for wastewater treatment of organic and biological contaminants, based on the cavitation water treatment is proposed in the paper. Theoretical knowledge and experimental researches in the field of cavitation has given ground to a method of vibro-resonance cavitation processing of liquids, which specific feature is organic combination of high-intensity of the formed cavitation field with significant treatment capacity. For its implementation, a low vibration electromagnetic resonance cavitator, which is of a simple structural design, energy saving and convenient in operation and maintenance was developed. The studies of vibrocavitation treatment efficiency, carried out on the dairy factory wastewater in the presence of nitrogen, indicate synergism of vibrocavitation action in the presence of gas that is confirmed by the calculated values of effective rate constants of microbial decontamination and destruction of organic compounds. The obtained results show high efficiency of wastewater treatment, conditioned by shock-dynamic, cavitation effects of sterilization and side phenomena of physical and electromagnetic nature, enhancing its effectiveness. Such integrated approach provides greater efficiency of the process on the whole process and opens the prospect of practical application in technologies of wastewater treatment at food enterprises.